The Implementation of Islamic Education Supervision: A Perspective Seen from Indonesian Case - Syafaruddin, Syafaruddin; Nurhasnawati, Nurhasnawati; Irawati, Irawati; Andriani, Tuti; Pratama, Melgis Dilkawaty (POTENSIA: Jurnal Kependidikan Islam, 2026)
This study aims to determine the implementation and supervision processes in the Islamic education environment. The role of supervisors is still considered negligible, especially in management and academic supervisions. There have been no serious efforts by the government to improve the supervisors’ performances. The recruitment process is also not unchanging in accordance with the standards set, even though work guidelines have been made. In the administrative aspects, they are more prominent than the aspects of services guidance of teachers’ professionalism. This research used a descriptive qualitative approach where a purposive sampling was used. The research informants included the head of the regional office of Ministry of Religious Affair in Pekanbaru, the head of the Islamic education department, the head of the supervisory team, the head and teachers of madrasah. Data collection techniques used interview, focus group discussion, and documentation. The data was analyzed by using Matthew and A. Michael Huberman’s model by reducing, presenting, and verifying the data. The study showed that the supervision process in Indonesia through three stage; the input stage where there was a lack of sources, and the process stage where supervision was carried out oriented to the instrument, and the output stage using an administrative approach. The study also found that the problems with supervision in Indonesia included lack of training at the input stage, lack of financial support at the process stage, and problems in the organizational structure at the output stage. It also found that the reconstruction of supervision in Indonesia carried out at the input and process stages was policy support, while at the output stage a restructuring was needed.